A Cross Sectional Study Of Thalassemia In Ahmedabad City, Gujarat. (Hospital based) - Shrenik Talsania; Niti Talsania; Himanshu Nayak (Indian Association of Preventive and Social Medicine, 2011)
Thalassemia is a quantitative problem of too few globins synthesized, whereas sickle-cell anemia (a hemoglobinopathy) is a qualitative problem of synthesis of an incorrectly functioning globin. The present study was undertaken with objective to study the occurrence and socio-demographic profile of thalassemia cases. There were 223 patients (55 from Municipal Corporation Hospitals & 168 from New civil hospital, Ahmedabad) admitted in the hospitals during January 2006 to March 2009.Majority of patients were males, from 1-5 year age group and from Hindu community. Majority of patients from corporation hospitals had more frequency of blood transfusion compared to government hospital. Thalassemia major cases were higher compared to minor.